Effect of operating parameters on the removal of bone cement by a sawing process. (March 2014) - James, Thomas P; Sheehan, Brian; Sagar, Amrit
The number of total knee arthroplasty revision surgeries is increasing each year, driven by the wide availability and general acceptance of the procedure accompanied by an aging population of implants. Metal implants are often secured to the tibial plateau by a mantle of poly(methyl methacrylate) bone cement. During revision surgery, a power oscillating saw is used to remove bone cement while preparing the boney bed. Presently, there are no published studies on the mechanics of bone cement removal by a sawing process. The aim of this research was to quantify the effect of blade speed and applied thrust force on the volumetric cutting rate of bone cement. A custom reciprocating saw with variable stroke length was used to conduct a three-factor design of experiments. Two levels, without center-points, were sufficient to model the effect of stroke length (6.75, 10.13 mm), thrust force (11, 19 N), and reciprocating speed in strokes per minute (6000, 8000 SPM) on cutting rate. The results indicate that each of the three parameters had a significant impact on cutting rate (p < 0.001), with a linear relationship between both force and cutting rate (r = 0.98) and blade speed and cutting rate (r = 0.98). For the parameters considered, increasing the reciprocating speed had the most significant effect on cutting rate. For example, while holding force and stroke length constant (11 N, 10.13 mm), an increase in speed from 6000 to 8000 SPM nearly doubled the cutting rate of bone cement. A cutting rate model was developed by regression analysis of the experimental data and validated through additional experiments. The model has applications in haptic feedback for surgical simulators to differentiate between the cutting rates of bone and bone cement during virtual training of resident surgeons.